Graduate Student’s Perception on Effectiveness of Virtual Education during Covid-19: Evidence from Structural Equation Modelling in Nepal - Adhikari, Bikash; Lawaju, Purnima; Adhikari, Kabita; Bohaju, Sabina (Quest Journal of Management and Social Sciences, 2024)
Background: The COVID-19 pandemic forced educational institutions worldwide to shift to online learning, disrupting traditional academic calendars. In Nepal, this transition significantly impacted graduate students, raising concerns about the effectiveness of virtual education. Objective: This study aims to examine the effectiveness of virtual education on student satisfaction and performance during the COVID-19 pandemic among graduate students in the Kathmandu Valley. Method: Based on the achievement goal theory, 203 graduate students from management colleges in Kathmandu Valley were selected through purposive sampling. Data were collected using a structured questionnaire administered via KOBO Toolbox. Both descriptive and inferential analyses, including Structural Equation Modeling (SEM), were employed to analyze the data. Result: The findings reveal that while the majority of students showed a positive attitude toward online classes, dissatisfaction arose due to a lack of training and familiarity with new information technologies. The SEM results indicate that course design, prompt feedback, and student expectations significantly influence student satisfaction, which in turn mediates the relationship between these factors and student performance. Challenges such as power outages, difficulty concentrating, lack of access to technology and insufficient instructor knowledge were identified as major obstacles. Conclusion: Although graduate students in Kathmandu Valley reported a generally positive outlook towards virtual education, several significant challenges need to be addressed to improve the effectiveness of online learning, particularly in terms of instructor quality and technological infrastructure. Paper Types: Research Paper Keywords: COVID-19, Virtual Education, Management Student, Effectiveness, Graduate Students Perception JEL Classification: D83, I20, L86, A23